The radioactive contamination territory of Ukraine by Pu and ²⁴¹Am radionuclides due to the Chernobyl accident - Kozhevnikova, M.F.; Levenets, V.V.; Rolik, I.L.; Shchur, A.A. (Вопросы атомной науки и техники, 2017)
The decay of β-emitting ²⁴¹Pu gives rise to long-lived α-radionuclides ²⁴¹Am and ²³⁷Np, which are highly radiotoxic. The estimations of the ²⁴¹Pu, ²⁴¹Am and ²³⁷Np content of the Chernobyl NPP accidental release have shown that by the present time nearly 90% of the ²⁴¹Pu isotope had already disintegrated to turn into ²⁴¹Am. This generates a need for developing the methods of analytical control and environmental monitoring of ²⁴¹Pu and ²⁴¹Am content. The present paper is concerned with estimation of radioactive contamination of the Ukrainian territory by ²⁴¹Pu and ²⁴¹Am isotopes as a result of the Chernobyl NPP accident.